2012
DOI: 10.1177/1741826711425338
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality and health status in cardiovascular disease populations: a meta-analysis of prospective studies

Abstract: Type D personality was shown to be an independent correlate of impaired patient-reported physical and mental health status in various cardiovascular patient groups. Clinicians should be aware of the association between chronic psychological distress and poor patient-reported outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 45 publications
(76 reference statements)
2
35
0
2
Order By: Relevance
“…These findings in general population coincide with the previous cross-sectional study in the United Kingdom (Williams et al, 2015). This personality type has been associated with a poorer physical health status (Versteeg et al, 2012), musculoskeletal pain and psychosomatic symptoms (Conden et al, 2013). It is counterfactual that people with Type D personality report worse lifestyle or health perceptions, but on the other hand the sample of people with cardiovascular diseases report similar Type D features to general population.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings in general population coincide with the previous cross-sectional study in the United Kingdom (Williams et al, 2015). This personality type has been associated with a poorer physical health status (Versteeg et al, 2012), musculoskeletal pain and psychosomatic symptoms (Conden et al, 2013). It is counterfactual that people with Type D personality report worse lifestyle or health perceptions, but on the other hand the sample of people with cardiovascular diseases report similar Type D features to general population.…”
Section: Discussionsupporting
confidence: 86%
“…However, the majority of the studies do not enrol people without obvious or specific health condition, making the research on Type D personality predominantly based on health disorders. This creates the situation where the prevalence of Type D in such samples is hard to compare with general population, even though it is largely accepted that Type D personality associates with worse physical and mental health (Versteeg, Spek, Pedersen, & Denollet, 2012). Regarding personality type, it is considered as relatively stable concept, with existing proofs on stability (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an additional criticism of Type D research is that the majority of studies investigating the influence of Type D on adverse clinical coronary outcomes have been conducted by a single group (Coyne et al, 2011;Smith, 2011). A recent meta-analysis which found support for a relationship between Type D personality and health status in coronary patients (Versteeg et al, 2012) was over-represented by studies from Denollet's group, whom also conducted the meta-analysis itself . However, this same criticism cannot be levelled at the body of research which has investigated the relationship between Type D and physiological functioning in healthy individuals, which has been conducted by several different research groups.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence has suggested a link between Type D and subjective health (including impaired physical health, increased symptoms of depression and anxiety, and lower quality of life) in CHF patients and those with peripheral arterial disease (PAD) [18][19][20][21][22]. Studies have also demonstrated the usefulness of the Type D construct in predicting subjective outcomes in post-MI patients.…”
Section: Introductionmentioning
confidence: 99%